Efficient Access to Deuterated and Tritiated Nucleobase Pharmaceuticals and Oligonucleotides using Hydrogen‐Isotope Exchange - Palazzolo, Alberto; Feuillastre, Sophie; Pfeifer, Viktor; Garcia‐Argote, Sébastien; Bouzouita, Donia; Tricard, Simon; Chollet, Céline; Marcon, Elodie; Buisson, David‐Alexandre; Cholet, Sophie; Fenaille, François; Lippens, Guy; et al. (Angewandte Chemie International Edition, 2019)
A general approach for the efficient hydrogen‐isotope exchange of nucleobase derivatives is described. Catalyzed by ruthenium nanoparticles, using mild reaction conditions, and involving either D2 or T2 as isotopic sources, this reaction possesses a wide substrate scope and a high solvent tolerability. This novel method facilitates the access to essential diagnostic tools in drug discovery and development: tritiated pharmaceuticals with high specific activities and deuterated oligonucleotides suitable for use as internal standards during LC‐MS quantification. Making the swap: A general approach for the late‐stage hydrogen‐isotope exchange of nucleobase derivatives is described. Catalyzed by ruthenium nanoparticles using mild reaction conditions and involving either D2 or T2 as isotopic sources, this reaction possesses a wide substrate scope and a high solvent tolerability. This novel method facilitates the access to essential diagnostic tools in drug discovery and development.